Dynamic changes in PSA levels predict prognostic outcomes in prostate cancer patients undergoing androgen -deprivation therapy: A multicenter retrospective analysis - Hu, Mingqiu; Mao, Yifeng; Guan, Chao; Tang, Zhizhong; Bao, Zhihang; Li, Yingbang; Liang, Guowu (Frontiers in Oncology, 2023)
ABSTRACT Background: Androgen-deprivation therapy (ADT) is used for the treatment of prostate cancer. However, the specific risk factors for the development of castration-resistant disease are still unclear. The present study sought to identify predictors of patient prognostic outcomes through analyses of clinical findings in large numbers of prostate cancer patients following ADT treatment. Methods: Data pertaining to 163 prostate cancer patients treated at the Second Affiliated Hospital of Bengbu Medical University and Maoming People's Hospital from January 1, 2015, to December 30, 2020, were retrospectively analyzed. Dynamic changes in prostate-specific antigen (PSA) levels were regularly assessed, including both time to nadir (TTN) and nadir PSA (nPSA). Univariate and multivariate analyses were performed with Cox risk proportional regression models, while differences in biochemical progression-free survival (bPFS) were compared among groups with Kaplan-Meier curves and log-rank tests. Results: The bPFS values over the median 43.5-month follow-up period differed significantly between patients with nPSA levels < 0.2 ng/mL and ≥ 0.2 ng/mL, being 27.6 months and 13.5 months, respectively (log-rank P < 0.001). A significant difference in median bPFS was also observed when comparing patients with a TTN ≥ 9 months (27.8 months) to those with a TTN < 9 months (13.5 months) (log-rank P < 0.001). Conclusions: TTN and nPSA are valuable predictors of prognosis in prostate cancer patients after ADT treatment, with better outcomes evident in patients with nPSA < 0.2 ng/mL and TTN > 9 months.